Medicine and Memory in Tibet Amchi Physicians in an Age of Reform - Hofer, Theresia (Studies on Ethnic Groups in China, 2018)
Only fifty years ago, Tibetan medicine, now seen in China as a vibrant aspect of Tibetan culture, was considered a feudal vestige to be eliminated through government-led social transformation. Medicine and Memory in Tibet examines medical revivalism on the geographic and sociopolitical margins both of China and of Tibet's medical establishment in Lhasa, exploring the work of medical practitioners, or amchi, and of Medical Houses in the west-central region of Tsang. Due to difficult research access and the power of state institutions in the writing of history, the perspectives of more marginal amchi have been absent from most accounts of Tibetan medicine. Theresia Hofer breaks new ground both theoretically and ethnographically, in ways that would be impossible in today's more restrictive political climate that severely limits access for researchers. She illuminates how medical practitioners safeguarded their professional heritage through great adversity and personal hardship.